The Application of Problem-Based Learning in Mathematics Education on Several South East Asia High Schools - Tri Dyah Prastiti; Dafik Dafik; Aldyon Restu Azkarahman (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Problem-based learning (PBL) is a learning method based on the process between learning material to real life problems. The method has been widely applied and shown positive results on different subjects and education levels. In this paper, we discuss the application of PBL in mathematics education on several high schools in South East Asia countries, which include Indonesia, Thailand, Malaysia, Singapore, and Vietnam, considering that all of the countries had close cultural and geographical aspects. Researches on the application of PBL showed overall positive results to the high school mathematics education in all of the observed countries, with similar and distinctive objective and outcomes were found. In Indonesia, the application of PBL in mathematics education improve student’s learning activities aside from its positive contribution to the learning outcomes, while in Thailand, Malaysia, and Singapore, PBL contributes to the improvement of students’ higher-order thinking skills.